2015
DOI: 10.1073/pnas.1415181112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of warming temperatures on US wheat yields

Abstract: Climate change is expected to increase future temperatures, potentially resulting in reduced crop production in many key production regions. Research quantifying the complex relationship between weather variables and wheat yields is rapidly growing, and recent advances have used a variety of model specifications that differ in how temperature data are included in the statistical yield equation. A unique data set that combines Kansas wheat variety field trial outcomes for 1985-2013 with location-specific weathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
290
7
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 371 publications
(314 citation statements)
references
References 33 publications
13
290
7
4
Order By: Relevance
“…We find that an additional DD above 33°C is associated with a 1.3% yield reduction (SI Appendix, Table S4). This extreme heat threshold is above ones identified for corn (29°C) and soybeans (30°C) but similar to ones identified for cotton (32°C), rice (33°C), and wheat (34°C) (20)(21)(22).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…We find that an additional DD above 33°C is associated with a 1.3% yield reduction (SI Appendix, Table S4). This extreme heat threshold is above ones identified for corn (29°C) and soybeans (30°C) but similar to ones identified for cotton (32°C), rice (33°C), and wheat (34°C) (20)(21)(22).…”
Section: Resultssupporting
confidence: 78%
“…As discussed in ref. 22, the management practices for the Kansas field trials vary by location and year and are considered "best management practices" as they are designed to eliminate all yield-reducing factors such as nutrient deficiencies or toxicities, damage from insect pests and disease, and competition from weeds. These optimal growing practices potentially differ from the production practices of actual farmers, who base management decisions on profitability.…”
Section: Increased Exposure To Extreme Heat Above 33°c Leads To Largementioning
confidence: 99%
“…These projections for wheat are similar to the 5.3% yield reduction per 1°C observed in Australia by Innes et al (2015) using a combination of experimental results coupled with simulation models. Tack et al (2015), using historical yield trials and meteorological data for Kansas, found a combination of freezing and warming impacts were responsible for yield variations. They observed a 40% reduction in wheat yields with a 4°C temperature increase and that newer varieties were less able to resist heat stress above 34°C than older varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Warming temperatures decreased USA wheat yields as observed by Tack et al (2015) using historical yield trials and meteorological data for Kansas. They used a combination of freezing and warming impacts in their regression model to evaluate yield trends and variation among years.…”
Section: Crop Progress and Productivitymentioning
confidence: 82%